Inclusive garment design for muslimah elderly with physical disabbilites in an Old Folks Home in Bangi, Selangor, Malaysia - Jamian, Juliza (2022)
World experiencing ageing growth as one of the global phenomenon by increasing the size and proportion in their population. This group of people facing various challenging issues in their life such as medical and health problem. This situation leads to ageing population who disabled and need more quality of care in their life. The chronic condition of disabled elderly cause a burden to them as for example disabled elderly having difficulties in control their body movement while handling dress and undress their garment. In addition, to ensure the high quality health system for disabled elderly in nursing or care unit, there is a need to improve assistive garment in order to provide ease of treatment access to disabled people in old folks home. The purpose of this study is to identify the best pattern design for garment to respect dignity of disabled elderly in folks home. Prior observation shows that, the problem of the existing opening of gowns that disabled elderly wear, effect on how disabled elderly wear the gowns while in the treatment centre or care centre. The health worker having difficulty in changing disabled elderly garment and have problem on the accessibility for medical examination. On a case study, a qualitative technique was applied literature research to create a suitable design pattern based on elderly need in the folks home. 15 respondents and 3 informants have contribuate idea and opinion in this study. Then, it employs observation and interview of the case on prototype to assess the improvement of the existing garment's everyday use. Finally, a semistructured questionnaire was used in the interview to assess the user's suitability for the proposed assistive garment. A sample of prototype been develop through out the process understanding elderly needs. It has been found that garment can contribute comfort and easy access for daily wear.